Assessment of Non-physical User Violence and Burnout in Primary Health Care Professionals. The Modulating Role of Job Satisfaction - Pina, David; Llor-Zaragoza, Paloma; López-López, Reyes; Ruiz-Hernández, Jose Antonio; Puente-López, Esteban; Galián-Munoz, Inmaculada; Martínez-Jarreta, Begoña (Frontiers in Public Health, 2022)
Introduction Growing concern about workplace violence shows the need for an evaluation in specific contexts in order to identify the particularities of each professional group. The health sector consists of a group of professionals with high exposure to violence, specially from users. There are differences depending on the professional category or unit in which the professional works. In this regard, Primary Health Care (PHC) is characterized by a personalized and continuous patient treatment over time, which is not exempt from cases of violence. Among the commonly studied consequences of these situations are decreases in job satisfaction and burnout. Objective The main objective of this study is to analyze the modulating role of job satisfaction in the relationship between non-physical user violence and the onset of burnout. Methods Cross-sectional comparative descriptive design. The sample consisted of 574 professionals from 39 PHC centers of the Murcian Health Service. Data were collected using two-stage cluster sampling. For data analysis, descriptive analysis, correlations and stepwise hierarchical regression were used to analyze the interaction between the variables. Results Regression analysis draws a model where non-physical violence and low intrinsic and extrinsic job satisfaction act as modulators of non-physical violence, cynicism and emotional exhaustion. Conclusions This study provides evidence of the psychological consequences of the perception of user violence in the PHC staff. Furthermore, it is evident that the emergence of burnout syndrome in these professionals is related to exposure to verbal or non-physical violence together with low job satisfaction. In this sense, a circular and bidirectional relationship between the variables studied is proposed as a possible explanatory model.